Epithelioid hemangioma involving three contiguous bones: A case report with a review of the literature - Vorachai Sirikulchayanonta (2018)
An epithelioid hemangioma involving three contiguous bones in continuity has, to the best of our knowledge, not been reported in the literature. A case of a 48- year-old man presented with radiating pain to the lower thoracic region for two years. A radiograph and CT scan revealed both permeative osteolytic and multiple trabeculated lesions involving the left posterior part of the 10th rib as well as the 9th and 10th vertebral bodies in continuity and was misled as a malignant or infectious lesion. The histopathology and immuno-histochemistry of the lesion confirmed the diagnosis of an epithelioid hemangioma. The lesion was still stableas of three years after surgery.